Quarrels and outrage in 1920s tango: Who sings in the “tangos of reproach” (Anclajes, 2024)
From its beginnings, the tango song configured certain characters and modulated different voices. In this context, during the 20s in the 20th century, flourished a set of compositions known as “tangos of reproach”, inheritors of the challenge tone of the gaucho literature. This work outlines this transfer and then deals with the subject who assumes the enunciation and the rhetoric deployed by the tangos of reproach, considering their conditions of circulation. The hypothesis is that tango did not reflect preexisting social identities, but instead played an active role in its production and presented them in a problematic way, in a cultural framework crossed by social, identity and political contradictions. We maintain that songs are intermedial and complex discursive objects, whose study cannot be reduced to textual analysis, since it must contemplate its performance and its circumstances of circulation.
Keywords: Tango Song; Social Identity; Enunciation; 20th Century; Argentina